Reconstructed springtime (March–June) precipitation tracked by tree rings dating back to 1760 CE in the Qinling-Bashan mountainous area - Wang, Shijie (2022)
In recent decades, considerable advances have been made in dendroclimatic reconstruction in the eastern monsoon region of China. However, understanding of long-term hydroclimatic changes has not been comprehensive due to the complexity of the regional geography in China's north-south transitional zone. Growth-climate response analysis indicated that springtime precipitation is the main factor limiting the radial growth of pine trees in the Qinling-Bashan mountainous area. Based on the three tree ring chronologies distributed in the southeast of Shaanxi Province, we developed a March–June precipitation reconstruction spanning 1760–2020 CE for the Qinling-Bashan mountainous area. Precipitation reconstruction accounts for 40.6% of the total precipitation variance during the instrumental period 1955–2016. Spatial correlation analysis indicated that the precipitation reconstruction recorded similar common precipitation signals for the eastern Qinling Mountains and the Yangtze-Huai River Basin. The results of the superposed epoch analysis (SEA) revealed that low precipitation was one of the main causes of severe drought and locust plague events. The preliminary synoptic climatology analysis showed that our reconstructed precipitation is closely linked to the El Niño-Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) variability.